Analisis Pembelajaran PKLH Secara Terintegrasi Dengan Pelajaran Lain Di SMP - Lullulangi, Mithen (Pascasarjana Universitas Negeri Makassar, 2018)
This study aims to determine the success of the program of Population and Environmental Education (PKLH) especially to evaluate the three main shutter in PKLH, ie cognitive shutter, affective shutter, and psychomotor shutter taught in an integrated manner with other subjects in Sekolah Menengah Pertama (SMP), Negeri 1 Balla Kecamatan Balla Mamasa Regency. The population of this study is all students of SMP Negeri 1 Balla, which consists of Class VII = 97 people, Class VIII = 88 people, so the population = 185 people. The sample in this study was determined by 134 students, taken by probability proportionate stratified random sampling. The research variables are: 1) The domain of thinking process (cognitive domain), 2) Affective domain and 3) the psychomotor domain of PKLH material. The data in this research is the result of the test to the respondent, that is the test done to know the knowledge, attitude, and skill of the students about things related to PKLH material. Data were analyzed descriptively and multiple regression using SPSS software as a tool. The results showed that: 1) The domain of the thinking process (cognitive domain), is in the low category, 2) Affective domain is in the medium category, and 3) The psychomotor domain is in the medium category. In addition, the result of multiple regression analysis shows that there is a significant relationship between the variables of thinking process and the sphere of attitude toward the skill domain, with an influence value of 68.4% about PKLH material.